Evaluation of Antimicrobial Activity and Cytotoxicity of an Epoxy Resin-Based Endodontic Sealer Containing Nanoparticles Amorphous Calcium Phosphate - Bilal H. Ibrahim; Hussain Al-Huwaizi (International Journal of Dentistry)
Background. The main cause of posttreatment disease in endodontics is the remaining of microorganisms within the root canal walls after endodontic therapy. Therefore, it is essential to use root canal sealers with potent antibacterial properties. These sealers play a vital role in eradicating any remaining microorganisms and preventing recontamination, especially in situations where there might be microleakage. Aim. The objective of this research was to examine the antimicrobial properties of epoxy root canal sealers containing nanoparticle amorphous calcium phosphate (NACP) against planktonic Enterococcus faecalis in a controlled laboratory environment. Furthermore, the study aimed to assess the potential cytotoxic effects of these sealers. Method. In order to determine the antimicrobial activity, the epoxy resin sealer (AH Plus, Dentsply, Germany) was supplemented with NACP from Sigma–Aldrich, at a concentration of 3wt.%, as per the previous flowability tests. The agar well diffusion assay method was employed to evaluate the antibacterial efficacy. For this, cultured plates (n = 8) were prepared, with each plate containing three wells: one with AH Plus, one with AH Plus + NACP, and one with NACP alone. Subsequently, the plates were sited at 37°C in an incubator and allowed to incubate overnight. The width of the inhibition zones was then analyzed and recorded by the SPSS statistical software package (Version 20.0 for Windows, SPSS, Chicago, IL, USA). The cytotoxicity of the NACP incorporated AH Plus and AH Plus sealers were tested indirectly by MTT assay and directly by the multiparametric high content screening toxicology assay using fibroblast-like cells as cell lines. Results. AH Plus + NACP showed a higher antimicrobial activity than AH Plus with significant difference (P<0.0001). Both materials showed nonsignificant difference compared to negative control, which indicated lower cytotoxicities. For AH Plus, P=0.3599,0.5959, and 0.4071, with time intervals 24, 72, and 168 hr, respectively. For AH Plus + NACP, P=0.4386,0.6182, and 0.2080, with 24, 72, and 168 hr, respectively. Conclusions. NACP incorporation with epoxy resin sealer AH PLUS had a higher antimicrobial activity with lower cytotoxic effect indicating their potential therapeutic values.